Peran Dinas Sosial dan Penanggulangan Kemiskinan Kota Bandung dalam Memberikan Perlindungan Hukum terhadap Anak Jalanan - Devita, Inna Aulia; Bisri, Lutfia Fauziah; Mahardika, Arida Putri; Sundani, Adinda Putri; Istiati, Rupaida; Ibtisam, M. Gilang Bayana; Nabila, Amanda Salsa; Yogatiyana, Nana (Lembaga Yasin AlSys, 2022)
Children are the hope and pioneer of the life of a country in the future, so a child has the right of their growth and development to obtain education, protection from violence, discrimination, and live in security and peace from various parties, namely family, community and government. This also applies to street children who are identical as a person/group of children who spend most of their time on the streets and come from various backgrounds, thus forcing them to be on the streets. Due to the increasing number of street children, it is necessary to get strict handling by not forgetting the rights that must be obtained. Bandung, which is one of the metropolitan cities in Indonesia, is the reason the researchers chose us in studying the problems regarding street children. This problem is studied based on the Perda Kota Bandung No. 4 Tahun 2019 concerning the Implementation of Child Protection which is the basis for handling street children problems carried out by the Dinas Sosial dan Penanggulangan Kemiskinan Kota Bandung. Researchers want to know what steps have been taken, obstacles and efforts that have been made. The research we conducted used a descriptive qualitative method with interview, observation, and documentation data collection techniques. From this, it was found that the steps or actions of the Dinas Sosial dan Penanggulangan Kemiskinan Kota Bandung in dealing with the problem of street children in accordance with the Perda Kota Bandung No. 4 Tahun 2019 concerning the Implementation of Child Protection is to form a USR Team and the construction of a Shelter House specifically intended for temporary shelter for the street children.